A PRODUÇÃO DO ESPAÇO PÚBLICO: DA DOMINAÇÃO À APROPRIAÇÃO - Sobarzo, Oscar (GEOUSP Espaço e Tempo (Online), 2006)
We propose an analysis of the public spaces through the point of view of the production of the space, that it relates the field activity of the dominance and of the appropriation. This approach is starting from the interpretation of the political dominance, of the capital accumulation and of the accomplishment of the people’s life. The political dominance refers us to the role of the elite’s political power in the production of the public space; also the capital accumulation, to the appearance of new products in the real estates market whose increase the reproduction and the circulation of the capital. This process question the relationship between what is public and private. Finally, it is discussing the sphere of the materialized human life realization in the public spaces which makes possible their daily practices. In that case, according to the quotidian there is changing the focus of the analyses of the public spaces of the dominance for appropriation, pointing out its importance in the production of people’s identity and appurtenance that allow to do the check list of the possibilities to overcoming or to subverting this process.